Global glacier surface elevation change and geodetic mass balance estimations - Malz, Philipp; Sommer, Christian; Seehaus, Thorsten; Farías-Barahona, David; Braun, Matthias (Proceedings of the European Conference on Synthetic Aperture Radar, EUSAR, 2021)
Glaciers worldwide undergo drastic adaption caused by climate change. A detailed knowledge about their status is of broad public interest, as glaciers are freshwater resources and drivers of sea level change. We aim at providing elevation change rates for mountain glaciers worldwide between 60° N and 56° S and respective geodetic mass balance. Therefore, we derive DEMs from TanDEM-X CoSSC datasets via own dInSAR processing. These DEMs are referenced, aligned and compared to SRTM V.3 DEMs. Resulting elevation change information are converted to mass balance and result to -64.5±2.8 Gt a-1 on 184,056 km2 (SRTM constraints).
CRIS-Team Scopus Importer:2021-06-04